Customer satisfaction/dissatisfaction with a brief introduction to loyalty - Oliver, Richard (Henry Stewart Talks, 2008)
Definition of satisfaction, Common models, Expectancy disconfirmation, Measurement, Operation of disconfirmation in determining satisfaction, Dissatisfaction, Complaint management model, Measurement of key concepts, Definition of loyalty, Stages and measurement, Relation of satisfaction to loyalty